Love, Aubrey - LaFleur, Suzanne M. (Wendy Lamb Books : Scholastic, Inc., 2009)
While living with her Gram in Vermont, eleven-year-old Aubrey writes letters as a way of dealing with losing her father and sister in a car accident, and then being abandoned by her grief-stricken mother.